Commentary: Iron deficiency of pregnancy - a new approach involving intravenous iron - Michael Auerbach (BMC, 2018)
Abstract Iron deficiency anemia of pregnancy is common, especially in South Asia, and is associated with adverse maternal and fetal outcomes including increased incidences of maternal mortality, preterm labor and low birth weight. Screening for anemia alone is not sufficient to diagnose iron deficiency. Iron deficiency in neonates is associated with a statistically significant increment in cognitive and behavioral abnormalities which persist after iron repletion. Oral iron is the frontline standard but is associated with an unacceptably high incidence of gastrointestinal adverse events leading to poor adherence. Prospective evidence reports an incidence of neonatal iron deficiency up to 45% even with oral iron supplementation. New evidence reports oral iron ingestion increases serum hepcidin leading to decreased absorption suggesting further decreasing efficacy. Published evidence reports that intravenous iron is safe and effective in the second and third trimesters of pregnancy. Intravenous iron is the preferred route when there is oral iron intolerance or in those situations where oral iron is ineffective or harmful. Intravenous iron is also preferred if the anemia is severe (< 8 g/dL) in the second trimester or at any time in the third trimester when there is little expectation that adequate quantities of iron will be delivered to the fetus as iron requirements increase in each trimester. Guidelines for maternal and neonatal screening and treatment lack consistency and differ between the United States and Europe. New formulations of intravenous iron with complex carbohydrate cores that bind elemental iron more tightly mitigating the release of large quantities of labile free iron allow the administration of complete replacement doses in 15-60 min. The preponderance of published evidence suggests that intravenous iron is underutilized in pregnancy and guidelines suggesting there is insufficient evidence to recommend the routine screening and treatment of iron deficiency in gravidas should be revisited. The major recommendation from this commentary is that in low-income countries, a trial or demonstration project to test the efficacy, safety, cost and feasibility of the administration of intravenous iron to anemic and/or iron-deficient women be undertaken.